Wellness profilok a magyar és az osztrák szállodaiparban - Varga, Nikolett; Molnár, Csilla (Acta Carolus Robertus, 2011)
In my work I present the Hungarian and Austrian wellness tourism, I try to set up an analyzing comparison mostly by introducing hotels that have special wellness profiles. The demand of the future tends to move towards health-tourism. The high standard and uniqueness of services is emphatic. In the present competition organizations can only survive if they provide something special, the perfect solution for this could be the formulation of a special wellness profile. Guests can find new, excellent quality services that meet the needs of the present age in a complex way. From this aspect our western neighbour means a serious concurrent, but also a must-follow example for our homeland. For keeping its competitiveness nowadays a service-provider should be able to meet the changing needs, provide new-type services and products, complex wellness tourism packages as well. In my thesis I show how diverse and colourful wellness hotels are, and what differences we can notice when comparing them with Austrian hotels. In the conclusion section of the thesis I intend to provide a solution, I state what changes I feel crucial in connection with the topic.